Clinical Outcomes after Clozapine Discontinuation in Patients with Schizophrenia: A Systematic Review - Miura, Gentaro; Tanaka, Kouhei; Kemuriyama, Takashi; Misawa, Fuminari; Uchida, Hiroyuki; Mimura, Masaru; Takeuchi, Hiroyoshi (Pharmacopsychiatry, 2022)
Introduction Clozapine is the gold standard of treatment for patients with treatment-resistant schizophrenia. However, approximately 60% of those patients do not respond to clozapine; moreover, clinical outcomes after clozapine discontinuation are unclear so far. Therefore, we conducted a systematic review to clarify the outcomes after clozapine discontinuation.Methods A systematic literature search was conducted, using MEDLINE and Embase with the following keywords: (clozapine AND (cessation* OR cease* OR withdraw* OR discontinu* OR halt* OR stop* OR switch*) AND (schizophreni* OR schizoaffective)).Results A total of 28 clinical studies from 27 articles were identified and included in this systematic review. Three randomized controlled trials reported worsening of psychiatric symptoms. In 10 single-arm studies, the results of worsening and improving psychiatric symptoms were inconsistent. In one large retrospective cohort study, clozapine rechallenge, olanzapine, and antipsychotic polypharmacy had lower rehospitalization rates compared to no medication after clozapine discontinuation. In the other 14 retrospective studies, the vast majority showed worsening of clinical status after clozapine discontinuation. Among five studies on clinical outcomes after clozapine rechallenge, four reported improvements in clinical status in more than half of patients who rechallenged clozapine. The remaining study reported that the clozapine discontinuation-rechallenge group had a worse remission assessment score than the clozapine discontinuation-no rechallenge group.Discussion Clinical outcomes generally worsen after clozapine discontinuation. Clozapine rechallenge and olanzapine may be considered following clozapine discontinuation. The outcomes after clozapine discontinuation in clozapine non-responders remain inconclusive; therefore, well-designed studies are warranted.
Keywords: cessation; clozapine; discontinuation; schizophrenia; treatment-resistant schizophrenia